Non-locality in the Science of the Millennium - Silvestrini, Paolo (Organisms. Journal of Biological Sciences, 2022)
The most recent experimental evidences of Quantum Physics and the new theoretical considerations connected to them have paradoxically questioned the basic founding principle of the scientific method, called the local realism principle. The main consequence of this cultural revolution is the need for a different approach to complexity in the world view through a phenomenon that I have called quantum synchronicity. Quantum synchronicity is a phenomenon that is associated with the principle of cause-effect and tells us that in the quantum world there is an intrinsic correlation between systems, not attributable to a recognizable and expressible physical interaction, which means that a quantum system, and in general the entire universe, cannot be traced back even in principle to a set of separable parts, which can be defined locally and interacting only according to causality. The non-local quantum vision has its laws, potentials and limits, which we are learning to know and use for our evolution. The possibilities are largely yet to be explored, and range from technological applications, such as the quantum computer that is almost ready to be commercialized with immense implications in information management, to a revolution in looking at our essence and the world that contains us as inseparable elements.